Pengaruh Pendidikan Karakter Terhadap Kesiapan Kerja Mahasiswa Pendidikan Kimia Universitas Islam Negeri Sunan Kalijaga - Muhammad Anarda Wiguna; Arnanda Irawan; Vikra Shafwa Humaira Sinambela; Ilham Aditya Anggara; Muhammad Zamhari (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This study investigates the connection between character education and the readiness for employment in the context of chemistry education students. The research employs a quantitative descriptive approach and a correlational method to examine this relationship. Sixty-nine chemistry education students were randomly selected from a population of 220 students through random sampling to participate in this research. The data collected were subjected to analysis using the Pearson Product-Moment correlation method. The analysis results unveiled a statistically significant positive correlation between character education and work readiness among chemistry education students (r = 0.532, p = 0.000 < 0.01). This outcome suggests that character education is associated with an improved state of preparedness for work among students. The implications of these findings emphasize the importance of incorporating character education into the chemistry education curriculum. Doing so is vital for equipping students with the holistic self-preparation necessary to succeed in a competitive job market and face the challenges of the professional world more effectively.